Evaluation of the Morphometric Measurements _x000D_ of Main Mediastinal Vascular Structures with _x000D_ Multi-detector Computed Tomography in Healthy _x000D_ Children - (:unkn) unknown (My University, 2021)
Objective: In this study, we aimed to evaluate the feasibility of the main pulmonary artery (MPA)/ascending aorta (AA) ratio measurement, which is 1:1 in adults, using the multi-detector computed tomographt in pediatric patients also. Method: The study was approved by the Institutional Review Board (number: 09.2016.014, approval date: 08.01.2016) and informed consent was waived since the study was retrospective. IV contrast-enhanced pulmonary computed tomography images of 487 pediatric patients (0-18 years), which had been performed between January 2015 and February 2016 in our center, were retrospectively evaluated. The diameters of the AA, MPA, right and left pulmonary arteries, and thoracic aorta were measured separately. Results: A positive correlation was determined between the diameters of mediastinal vascular structures and the patient age. The MPA/AA ratio was higher in the pediatric group when compared to adults, and this ratio was found to be higher than 1 in all pediatric cases. Conclusion: The higher diameter of MPA when compared to AA in pediatric cases is thought to be responsible for MPA/AA ratio being greater than 1, and that should not be considered as pulmonary hypertension. We suggest a threshold of 1.06 for the MPA/AA ratio regarding the diagnosis of PH.

Amaç: Çalışmada multi-dedektör bilgisayarlı tomografi kullanarak, _x000D_ erişkin yaş grubunda 1:1 olan ana pulmoner arter (APA)/asendan aorta _x000D_ (AA) oranının pediyatrik yaş grubunda uygulanabiliyor olup olmadığını _x000D_ araştırmayı amaçladık._x000D_ Yöntem: Çalışma için, Klinik Araştırmalar Etik Kurulu tarafından _x000D_ 08.01.2016 tarihinde 09.2016.014 sayılı yazı ile onay verilmiştir. Ocak 2015 _x000D_ ile Şubat 2016 tarihleri arasında hastanemize başvuran ve kontrastlı _x000D_ akciğer bilgisayarlı tomografisi çekilen pediyatrik yaş grubundan (0-18 _x000D_ yaş) 487 olgunun görüntüleri retrospektif olarak değerlendirilmiştir. AA, _x000D_ APA, sağ pulmoner arter, sol pulmoner arter, torasik aorta ve torasik _x000D_ vertebra çapları ayrı ayrı ölçülmüştür._x000D_ Bulgular: Ölçülen mediastinal vasküler yapı çapları ve hasta yaşı _x000D_ arasında pozitif korelasyonun varlığı tespit edilmiştir. APA/AA oranının, _x000D_ pediyatrik yaş grubunda erişkin yaş grubuna göre anlamlı olarak yüksek _x000D_ olduğu tespit edilmiştir. Çalışmamızda bu oran tüm pediyatrik yaş grupları _x000D_ arasında 1’in üzerinde bulunmuştur._x000D_ Sonuç: Pediyatrik yaş grubunda APA’nın AA çapından daha geniş olması _x000D_ nedeniyle APA/AA oranının 1’in üzerinde olan tüm olgularda pulmoner _x000D_ hipertansiyon ön tanısında bulunulmamalıdır. Bu oranın eşik değerinin _x000D_ 1,06 olarak kabul edilebileceğini önermekteyiz.
Sağlıklı Çocuklarda Mediastinal Ana Vasküler Yapıların Multi-dedektör Bilgisayarlı Tomografi ile Değerlendirilmesi